Increasing competitive advantage in Binong tourism village with the implementation of digital brand destination - S.E., M.M, Astri Wulandari; M. Si, Riska Aprilina, S.T.; Marcelino, S.A.B., M.M, Dandy (Edelweiss Applied Science and Technology, 2025)
The potential of Binong Tourism Village is very large with the various knitting products produced and the existing tourist attractions. It is hoped that this potential will be known to the public so that it will increase their interest and interest in visiting Binong Tourism Village. Digital Brand Destination is a strategy to increase branding by utilizing digital media. This research aims to improve the branding of Binong Tourism Village with a Digital Brand Destination strategy which can also be a competitive advantage, and increase tourist experience. The research was carried out in various stages, starting from conducting focus group discussions and interviews with the Binong Tourism Village, then pre-survey, taking photos and videos for marketing content, creating a Digital Marketing Plan, creating a Business Model Canvas, utilizing digital media, using Ads features until later training and mentoring will be held for MSME players there. This research using qualitative and quantitative data. Qualitative data based on interviews with the Binong Tourism Village. Quantitative data was obtained by distributing questionnaires to 100 respondents. The data used is primary data and secondary data. A pre-survey was also carried out to find out the hopes of partners and the general public for developing the potential of Binong Tourism Village in the future. The next step is to create a digital marketing plan by analyzing the advantages, disadvantages, opportunities and challenges of Binong Tourism Village both externally and internally. Furthermore, data and analysis will also be obtained from the Business Capital Canvas. Based on several stages of research that have been carried out, it shows that Binong Tourism Village has great tourism potential, but has not yet maximized the use of digital media as a means of promotion and branding. A Digital Marketing Plan and Business Model Canvas scheme been created to develop digital branding as a competitive advantage and an indicator of improving the tourist experience when visiting Binong Tourism Village. So, it is hoped that the development of a digital brand destination can increase public awareness of the potential of Binong Tourism Village, and can increase the reach of promotions and branding.